Utilization of Different Preservatives (Cloves and White Pepper) for Extending of Shelf Life and Nutritional Value of Tiger Nut Milk (Kunun Aya) - Yusuf, Obadiah Saveni; Abershi, Ajiduku Leyoa; Ngabea, Nasiru Audu; Bappa, Lipana Dorcas; Dauda, Usman Danlami; Chuanu, Solomon; Mafe, Alice Njolke; Titus, Stephen Dio; Sambo, Elkanah Deborah; Garba, Haladu Farida (Darul Yasin Al Sys, 2024)
Tiger nut milk (Kunun aya) is a traditional beverage and its non-alcoholic widely consumed in Northern part of Nigeria. The beverage was prepared from tiger nut with addition of spices such as cloves, and white pepper at different concentration in order to find its natural preservatives, so as to be preserve for a longer period using natural material so as to find if its shelf life and nutritional content will be maintained. The samples were stored at 4o c for 2 days and the effects of those spices on their proximate, microbial and fungal counts were evaluated. Fresh tiger nut and the spices (cloves and white pepper) were purchased form Jalingo central market in Taraba state in the Northeastern part of Nigeria. The tiger nut milk seeds were sorted and all the unwanted materials which may affects the taste and keeping quality of the drink were removed, washed and rinsed with portable water and then soaked for eight hours(8hrs) to soften the fibre and to remove off-flavor. One kilogram of fresh tiger nut was blended four times in to slurry with water. The slurry was pressed using a muslin cloth to recover extract. Two samples of spiced drink were analyzed for total moisture, ash content, crude protein, crude fibre, crude fat, and carbohydrate. Results of the proximate analysis reveal a range of 80.0-89.5% and 79.8- 87.2% and for moisture of tiger nut milk with cloves and white pepper which is higher at tiger nut with cloves. Ash content ranged from 0.3 -0.6 and 0.6-0.8%, both shows no significant difference in both sample B(1g) of tiger nut milk with cloves and white pepper. For crude fat it ranges 2.5-4.8%, and 2.3-4.1%. The crude fibre shows 2.1-3.0 and 2.2-3.2%, then crude protein 3.3-3.7% and 3.0-3.9% and carbohydrate range 1.7-3.9% and 1.9-2.6% of tiger nut milk cloves and white pepper respectively with no significant difference in sample C(2g) and control in tiger nut milk with cloves under carbohydrate content. The bacterial count of tiger nut milk with cloves and white pepper range 1.2×104 -2.7×104 and 1.6×104-3.0×104 respectively. And fungal count 1.5×107 -2.1×107 and 1.8×107 -2.1×107 with no significant difference in sample B(1g) and C(2g) with both have 1.8×107. The study revealed that cloves and white pepper can be served as a natural preservative in tiger nut milk and at the same time maintain its nutritional qualities.